Hospital Care Cost Analysis of Normal Delivery of Migrant Workers, Fiscal Year 2015: a Case Study of Ko Chang Hospital, Trat Province - Chownna, Saowapa; Kongsin, Sukhontha; Jiamton, Sukhum; Leaungsomnapa, Yosapon (Journal of Health Science of Thailand, 2018)
The objective of this study was to analyze hospital care cost of Ko Chang Hospital for normal delivery of migrant workers in fiscal year 2015 under provider perspectives. Migrant women who were covered by migrant health insurance fund were recruited. The participants were 84 migrants who visited the hospital and had normal delivery from October 2014 to September 2015. Health care were provided by 29 hospital personnel including doctors, nurses, and nurse-aids. The overall hospital care cost of normal delivery among 86 migrant workers in fiscal year 2015 was 887,372.92 baht, comprised of operating cost of 829,543.11 baht (93.4%), material cost of 23,622.77 baht (2.6%), and capital cost of 34,207.04 baht (3.8%). The ratio of labor cost : material cost : capital cost was 35.12 : 1.00 : 1.45. Unit cost of normal labor was 10,563.96 per case or 3,841.44 baht per admission-day. The study revealed that the budget the hospital received from migrant insurance fund was lower than the over all hospital care cost of normal delivery among migrant workers. The cost charge ratio was less than 1, thus the capitation allocated to the hospital from migrant insurance was less than the unit cost of normal delivery of migrant workers. The hospital administrators should convey the results from this study to the health insurance office of the Ministry of Public Health to consider the burden the hospital when providing care for normal delivery among migrant workers, and to request for adjustment in the reimbursement of the hospital costs.